Sanctions for Rape Crime in Decision Number 156/Pid.Sus/2020/PN.Pkb. Perspective of Islamic Criminal Law - Kusuma, Fajar Ichsan; Anwar, Syahrul; Najmudin, Deden (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
Rape is a serious crime that violates the law and human dignity. However, court rulings, such as Decision No. 156/Pid.Sus/2020/PN.Pkb, often impose light sentences that are not commensurate with the serious impact experienced by the victims. This study aims to examine the chronology of the case, the reasons behind the judge's decision to impose a lenient sentence, the impact of the decision on crime prevention, as well as the elements and penalties for the crime of child rape under the perspective of Islamic Criminal Law. Using a case approach, normative legal methodology, and qualitative data, the data was collected through library research and analyzed using content analysis. This study draws on modern legal theory, the theory of Maqashid Syariah, and the theory of jarimah ta'zir. The findings reveal a significant imbalance between the severity of the criminal act and the leniency of the imposed sanctions, which undermines the objectives of modern legal theory and the theory of Maqashid Syariah. In this case, the defendant was sentenced to six years in prison, despite the applicable law (Article 81(3)) allowing for a maximum sentence of fifteen years. Furthermore, Islamic law does not explicitly stipulate punishment for rape in the Quran, scholars analogize it to the law of adultery as outlined in the Quran, Surah An-Nur, Verse 2. As for the Hadith narrated by Muhammad bin Yahya Al-Naisaburi, it supports similar penalties for rape and adultery, with the main difference being that only the perpetrator is punished.